(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article examines the importance of enhancing software and methodological support in preparing future informatics teachers for independent research activities. As digital technologies become an integral part of modern education, the demand for educators who are capable of conducting research, analyzing data, and applying innovative approaches to teaching is increasing. The study focuses on developing a comprehensive framework that integrates digital tools, pedagogical strategies, and methodological principles to support students’ research competencies. Based on an analysis of the current educational standards and the experience of pedagogical institutions in Uzbekistan, the article proposes several improvements in instructional design, digital content development, and interactive research platforms. The goal is to ensure that pre-service teachers in the field of informatics are equipped with the skills, tools, and methodologies needed for productive and autonomous scholarly inquiry.